Anti-glomerular basement membrane (anti-GBM) disease accompanied by vasculitis that was not positive for antineutrophil cytoplasmic antibodies to myeloperoxidase and proteinase 3 : a report of two cases and the incidence of anti-GBM disease at one institution - Nakabayashi, Kimimasa; Fujioka, Yasunori; Arimura, Yoshihiro; Fukuoka, Toshihito; Marumo, Tomohumi; Umino, Michiru; Kamiya, Yasushi; Okai, Takahiro; Tsurumaki, Shigeru; Nagasawa, Toshihiko; Yamada, Akira (Clinical and experimental nephrology, 2011)
Background Anti-glomerular basement membrane (anti-GBM) disease is thought to be distinct from vasculitis. In contrast, there have been several papers suggesting the presence of angiitis in cases that were positive for anti-GBM antibody (Ab), as well as for either myeloperoxidase (MPO)- or proteinase 3 (PR3)-anti-neutrophil cytoplasmic antibody (ANCA) (Group I). We experienced four patients who had anti-GBM Abs, but not MPO- and PR3-ANCA (Group II), and two of these patients were found to have vasculitis. Therefore, we performed an in-depth study on these two patients. Methods The patients with anti-GBM disease were isolated from 578 cases whose renal tissues were examined, and they were categorized into two groups. We have already published the data about Group I. We then proceeded to study two vasculitic patients in Group II clinically, pathologically, and serologically. The anti-GBM Ab and ANCA levels were detected by enzyme-linked immunosorbent assays. Renal specimens were studied by routine staining as well as immunohistochemical investigations of CD31 and type IV collagen. Results The total number of patients with anti-GBM disease was 7 (7/578 = 1.2%), with 3 patients belonging to Group I and 4 patients belonging to Group II. Two patients in Group II were diagnosed to have vasculitis, but the remaining 2 patients did not. One vasculitic patient was complicated by pulmonary hemorrhage, while the other vasculitic patient displayed peripheral neuropathy as well as a small cavity lesion in the lung. The latter patient was found to be positive for perinuclear (p)-ANCA, but not for any other ANCA subsets. The renal pathology in the two vasculitic patients showed crescentic glomerulonephritis (CSGN) and immunoglobulin (Ig) G linear deposits along the glomerular capillary loops. The former patient showed fibrinoid angiitis in an afferent arteriole as well as peritubular capillaritis. The latter patient demonstrated peritubular capillaritis. These peritubular capillaritides were diagnosed by the loss of CD31 and type IV collagen staining, the blurred appearance of peritubular capillary walls by periodic acid-Schiff staining, and the pericapillary infiltration of inflammatory cells. Conclusion The incidence of anti-GBM disease was very low, and our patients were categorized into two groups (Groups I and II) based on whether or not they were positive for MPO- or PR3-ANCA. Two patients in Group II were found to have vasculitis. According to our results, we concluded that the anti-GBM disease of Group II could also be associated with vasculitis.